UNDERSTANDING OF MATHEMATICAL CONCEPTS IN TERMS OF STUDENT LEARNING INTEREST USING THE TEAMS GAMES TOURNAMENTS MODEL ASSISTED BY SPORCLE - Wibowo, Muhammad Umar; Maryono, Iyon; Widiastuti, T Tutut (Math Educa Journal, 2024)
Mathematical Conceptual Understanding (KPKM) of students needs to be improved because it is essential for their skills. This study aims to enhance KPKM by using the Teams Games Tournaments model through Sporcle (TGTS). The TGTS model was chosen because it combines elements of competition and games that can increase student participation and interest in learning. The method used is a quasi-experiment with the population consisting of all class X MIPA students in two classes, while the samples were class X MIPA 1 as the experimental class and X MIPA 2 as the control class. Data were collected through student activity observation sheets, pretests and posttests, and learning interest questionnaires. After the research was conducted, data on student activity and learning interest were analyzed descriptively, while pretest and posttest data were analyzed using the independent t-test, two-way ANOVA, and N-gain. The results showed a significant difference in KPKM between students who learned using the TGTS model and those who learned with the conventional model. The results also showed that there was no significant interaction effect between the TGTS learning method and the level of students' learning interest on KPKM. This indicates that the TGTS model had a positive impact on students' mathematical conceptual understanding consistently, regardless of their learning interest level, whether high, medium, or low.